The Effect of Progressive Muscle Relaxation Technique on Anxiety Levels in Chronic Kidney Failure Patients Undergoing Hemodialysis at Gatot Soebroto Army Hospital - Gusti Ayu Tri Shita Devi; Bahreni Yusuf; Hendik Wicaksono (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Bacground: Patients with chronic kidney disease undergoing hemodialysis frequently experience anxiety duet o the continuous nature of the therapy. Progressive muscle relaxation techniques are used to help reduce anxiety by controlling muscle tension and regulating patients emotional responses. Objective: To determine the effect of progressive muscle relaxation techniques on anxiety levels among patients with chronic kidney disease undergoing hemodialysis at RSPAD Gatot Soebroto. Methods: This study employed a pre experimental one group pretest-posttest design, total sampling was used, involving 21 respondents who met the inclusion and exclusion criteria. The Hamilton Anxiety Rating Scale (HARS) was utilized to measure anxiety levels during the pretest and posttest. Data analysis was performed using the Wilcoxon Signed Rank Test. Results: A reduction in anxiety levels was observed. During the pretest, 16 respondents experienced mild anxiety and 5 respondents experienced moderate anxiety. After the intervention, anxiety levels decreased, with 19 respondents experiencing no anxiety and 2 respondents experiencing mild anxiety. Conclusion: Progressive muscle relaxation techniques significantly reduced anxiety levels in patients undergoing hemodialysis, with a p-value of 0.00 (p < 0.05). Recommendation: This study provides evidence that progressive muscle relaxation is an effective, safe, and simple non-pharmacological intervention for reducing anxiety in patients with chronic kidney disease undergoing hemodialysis, and may serve as a reference for clinical practice, patient self-management, and future research.